Prosperity as an American Dream: A Study on Ben Fowlkes’S You’Ll Apologize If You Have To - Hafshah, Maulita Ridha; Harendika, Melania Shinta (Universitas Negeri Semarang, 2021)
You’ll Apologize If You Have To (2015), a short story by Ben Fowlkes, portrays the struggle of an American in pursuing his dreams. The primary data of this research is the narration and dialogues uttered by the characters: Wallace, Kim, Molly, the Old Lady, and the Green-Jacket Man. Those data are classified based on the American dreams (Adams, Franklin, Jefferson, Livingston, & Sherman, 2014; Cullen, 2003; Mailer, Thompson, & Wolfe, 2009), specifically those related to material wealth. The result of this research reveals that in their daily life, the characters have their perspectives on seeing America as the land of dreams. Generally, they dream of a better life and happiness. However, this short story also portrays American dreams as a paradox because not all Americans have the privilege to achieve those dreams.